An Azole-Resistant Candida parapsilosis Outbreak: Clonal Persistence in the Intensive Care Unit of a Brazilian Teaching Hospital - Thomaz, Danilo Yamamoto; de Almeida, João Nobrega; Lima, Glaucia Moreira Espindola; Nunes, Maína de Oliveira; Camargo, Carlos Henrique; Grenfell, Rafaella de Carvalho; Benard, Gil; Del Negro, Gilda M. B. (Frontiers in Microbiology, 2018)
The incidence of candidemia by the C. parapsilosis complex has increased considerably in recent decades, frequently related to use of indwelling intravascular catheters. The ability of this pathogen to colonize healthcare workers’ hands, and to form biofilm on medical devices has been associated with the occurrence of nosocomial outbreaks and high mortality rates. Fluconazole has been the leading antifungal drug for the treatment of invasive candidiasis in developing countries. However, azole-resistant C. parapsilosis isolates are emerging worldwide, including in Brazil. Few studies have correlated outbreak infections due to C. parapsilosis with virulence factors, such as biofilm production. We thus conducted a microbiological investigation of C. parapsilosis complex isolates from a Brazilian teaching hospital. Additionally, we identified a previously unrecognized outbreak caused by a persistent azole-resistant C. parapsilosis (sensu stricto) clone in the intensive care unit (ICU), correlating it with the main clinical data from the patients with invasive candidiasis. The molecular identification of the isolates was carried out by PCR-RFLP assay; antifungal susceptibility and biofilm formation were also evaluated. The genotyping of all C. parapsilosis (sensu stricto) was performed by microsatellite analysis and the presence of ERG11 mutations was assessed in the azole non-susceptible isolates. Fourteen C. parapsilosis (sensu stricto) isolates were recovered from patients with invasive candidiasis, eight being fluconazole and voriconazole-resistant, and two intermediate only to fluconazole. All non-susceptible isolates showed a similar pattern of biofilm formation with low biomass and metabolic activity. The A395T mutation in ERG11 was detected exclusively among the azole-resistant isolates. According to the microsatellite analysis, all azole non-susceptible isolates from the adult ICU were clustered together indicating the occurrence of an outbreak. Regarding clinical data, all patients infected by the clonal non-susceptible isolates and none of the patients infected by the susceptible isolates had been previously exposed to corticosteroids (p=0.001), while the remaining characteristics showed no statistical significance. The current study revealed the persistence of an azole non-susceptible C. parapsilosis clone with low capacity to form biofilm over two years in the adult ICU. These results reinforce the need of epidemiological surveillance and monitoring antifungal susceptibility of C. parapsilosis isolates in hospital wards.